Immunosuppressive capacity of circulating MDSC predicts response to immune checkpoint inhibitors in melanoma patients - Petrova, Vera; Groth, Christopher; Bitsch, Rebekka; Arkhypov, Ihor; Simon, Sonja C. S.; Hetjens, Svetlana; Müller, Verena; Utikal, Jochen; Umansky, Viktor (Frontiers in Immunology, 2023)
Purpose: Although the treatment of advanced melanoma patients with immune checkpoint inhibitors (ICI) significantly increased the therapeutic efficiency, many patients remain resistant to ICI that could be due to immunosuppression mediated by myeloid-derived suppressor cells (MDSC). These cells are enriched and activated in melanoma patients and could be considered as therapeutic targets. Here we studied dynamic changes in immunosuppressive pattern and activity of circulating MDSC from melanoma patients treated with ICI. Experimental Design: MDSC frequency, immunosuppressive markers and function were evaluated in freshly isolated peripheral blood mononuclear cells (PBMC) from 29 melanoma patients receiving ICI. Blood samples were taken prior and during the treatment and analyzed by flow cytometry and bio-plex assay. Results: MDSC frequency was significantly increased before the therapy and through three months of treatment in non-responders as compared to responders. Prior to the ICI therapy, MDSC from non-responders displayed high levels of immunosuppression measured by the inhibition of T cell proliferation assay, whereas MDSC from responding patients failed to inhibit T cells. Patients without visible metastasis were characterized by the absence of MDSC immunosuppressive activity during the ICI treatment. Moreover, non-responders showed significantly higher IL-6 and IL-8 concentrations before therapy and after the first ICI application as compared to responders. Conclusions: Our findings highlight the role of MDSC during melanoma progression and suggest that frequency and immunosuppressive activity of circulating MDSC before and during the ICI treatment of melanoma patients could be used as biomarkers of response to ICI therapy.